The information needs and use patterns of the Manila Electric Company employees who use the MERALCO Central Library - Villarin, Victor T. (Institute of Library Science, University of the Philippines Diliman, 2002)
The main objective of the study was to determine the information needs and use patterns of the Manila Electric Company (MERALCO) employees who use the MERALCO Central Library. In particular, it sought to find out their corporate department affiliation, their job level position, as well as their age and sex, and the relationship of these two areas of knowledge, sources, types and forms of their needed information, and to the dependent variables of frequency of use, success in information searching and level of satisfaction with library services. Determining their motives and purposes in using the Central Library, their techniques and methods for searching information and their suggestions for library improvements were also considered.